Ultrahigh‐cell‐density heterotrophic cultivation of the unicellular green microalga Scenedesmus acuminatus and application of the cells to photoautotrophic culture enhance biomass and lipid production. Issue 1 (12th November 2019) - Jin, Hu; Zhang, Hu; Zhou, Zhiwei; Li, Kunpeng; Hou, Guoli; Xu, Quan; Chuai, Wenhua; Zhang, Chengwu; Han, Danxiang; Hu, Qiang
Abstract: Although production of biodiesels from microalgae is proved to be technically feasible, a commercially viable system has yet to emerge. High‐cell‐density fermentation of microalgae can be coupled with photoautotrophic cultivation to produce oils. In this study, by optimizing culturing conditions and employing a sophisticated substrate feed control strategy, ultrahigh‐cell‐density of 286 and 283.5 g/L was achieved for the unicellular alga Scenedesmus acuminatus grown in 7.5‐L bench‐scale and 1, 000‐L pilot‐scale fermenters, respectively. The outdoor scale‐up experiments indicated that heterotrophically grown S . acuminatus cells are more productive in terms of both biomass and lipid accumulation when they are inoculated in photobioreactors for lipid production as compared to the cells originally grown under photoautotrophic conditions. Technoeconomic analysis based on the pilot‐scale data indicated that the cost of heterotrophic cultivation of microalgae for biomass production is comparable with that of the open‐pond system and much lower than that of tubular PBR, if the biomass yield was higher than 200 g/L. This study demonstrated the economic viability of heterotrophic cultivation on large‐scale microalgal inocula production, but ultrahigh‐productivity fermentation is a prerequisite. Moreover, the advantages of the combined heterotrophic and photoautotrophic cultivation of microalgae for biofuels production were also verified in the pilot‐scale. Abstract : Jin and coworkers optimized heterotrophic culturing conditions for the unicellular alga Scenedesmus acuminatus, and developed the sophisticated substrate feed control strategy enabling the maximum biomass concentration of 286 and 283.5 g L −1 in 7.5‐L bench‐scale and 1, 000‐L pilot‐scale fermenters, respectively. The authors observed that the heterotrophically grown algal cells produced more lipids than the photoautotrophic counterpart in the pilot‐scale photobioreactors. This study demonstrated the economic viability of heterotrophic cultivation on large‐scale microalgal inocula production, but ultra‐high‐productivity fermentation is prerequisite.